The David Livingstone Spectral Imaging Project. - Rubery, Matthew (Scottish Geographical Journal)
The article discusses the launch of the David Livingstone Spectral Imaging Project to restore the selected writings of Scotland's abolitionist, missionary and explorer. It highlights the use of spectral imaging technology into a series of faded, illegible text written during the final African expedition. It notes that the images maintain the forms of textual manipulation, comparison and searching in print formats.